Properties of electromagnetic waves that propagate along the left-hand material slab - Azarenkov, N.A.; Akimov, Yu.A.; Galaydych, V.K.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2009)
This report is devoted to the investigation of the dispersion and the spatial distribution of the electromagnetic field of the surface type waves that propagate along the planar waveguide structure. This structure consists of the left-handed material slab, bounded by the semi-infinite regions of ordinary dielectric with constant permittivity and permeability. The wave considered propagates along the interface between left and right handed materials. The obtained results can be useful for the future image processing applications. Досліджуються дисперсійні властивості та просторовий розподіл електромагнітного поля хвилі, що поширюється в пласкій хвилеводній структурі. Структура, що розглядається, складається з шару лівого плазмоподібного середовища, що знаходиться в діелектрику зі сталими значеннями діелектричної та магнітної проникностями. Хвилі, що досліджуються, поширюються уздовж межі розподілу ліве середовище –діелектрик. Отримані результати можуть бути використані у системах передачі інформації, обробці зображень, та ін. Исследуются дисперсионные свойства и пространственное распределение электромагнитного поля волны, распространяющейся в плоской волноводной структуре. Рассматриваемая структура состоит из слоя левой плазмоподобной среды, размещенной в диэлектрике с постоянной диэлектрической и магнитной проницаемостями. Исследуемые волны распространяются вдоль границы раздела левая среда – обычный диэлектрик. Полученные результаты могут быть использованы в системах передачи информации, обработке изображений и т.п.